Global Vision and Local Action: Football, Corruption and the Governance of Football in China. Issue 2 (4th May 2022) - Wang, Runbin; Ren, Zhenpeng
Abstract: The professional reform of Chinese football was a pilot project for the transformation of China's sports system. However, the reform was limited by the confused role of governance bodies, which subsequently led to weak governance in relation to Chinese football-corruption. In order to examine existing problems in football governance and corruption in Chinese football a thematic analysis was performed, taking the five basic elements of governance (governance object, governance subject, regulation text, governance value, and governance effect) as the analytical framework. This provides the basis for an objective assessment of the existing structure of governance dealing with corruption in Chinese football. The measures and experiences related to addressing football corruption in Europe and other Asian countries are also discussed. Based on historical comparisons within the Chinese context as well as the lessons drawn from other countries, a plan for the future implementation of anti-corruption measures and reforms in Chinese football is outlined, including the coordination and cooperation of governance subjects, the revision and improvement of regulatory text, governance value-orientation toward democracy, and rulings based on law and accountability.